1999
DOI: 10.1038/23060
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 induces skeletal myocyte hypertrophy through calcineurin in association with GATA-2 and NF-ATc1

Abstract: Localized synthesis of insulin-like growth factors (IGFs) has been broadly implicated in skeletal muscle growth, hypertrophy and regeneration. Virally delivered IGF-1 genes induce local skeletal muscle hypertrophy and attenuate age-related skeletal muscle atrophy, restoring and improving muscle mass and strength in mice. Here we show that the molecular pathways underlying the hypertrophic action of IGF-1 in skeletal muscle are similar to those responsible for cardiac hypertrophy. Transfected IGF-1 gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
473
5
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 596 publications
(504 citation statements)
references
References 33 publications
21
473
5
4
Order By: Relevance
“…In particular IGF-1 is a growth stimulating agent for muscle cells in vitro [11,25,28,35] and in vivo [3], although the in vivo role of IGF-1 in stimulating muscle growth in adult animals is less clear and may rely in part on the presence of growth hormone [21]. Recent evidence also suggests that muscle growth in response to stretch is associated with the expression of an alternatively spliced form of IGF-1 [15,39].…”
Section: Discussionmentioning
confidence: 99%
“…In particular IGF-1 is a growth stimulating agent for muscle cells in vitro [11,25,28,35] and in vivo [3], although the in vivo role of IGF-1 in stimulating muscle growth in adult animals is less clear and may rely in part on the presence of growth hormone [21]. Recent evidence also suggests that muscle growth in response to stretch is associated with the expression of an alternatively spliced form of IGF-1 [15,39].…”
Section: Discussionmentioning
confidence: 99%
“…In cardiac muscle, calcineurin signalling is necessary for cardiomyocyte maturation, heart chamber formation and cardiac hypertrophy (Schulz and Yutzey, 2004). In skeletal muscle, calcineurin appears to be needed in a number of key developmental processes, namely enhanced muscle cell differentiation, and in the fibre type context, conversion to slow (oxidative) muscle phenotype (Musarò et al, 1999;Semsarian et al, 1999;Bigard et al, 2000;Delling et al, 2000). It has been reported that activated calcineurin mediates the hypertrophic effect of IGF-1 (Musarò et al, 1999;Semsarian et al, 1999).…”
Section: Fibre Types: Coordinated Isoform-specific Expressionmentioning
confidence: 99%
“…In skeletal muscle, calcineurin appears to be needed in a number of key developmental processes, namely enhanced muscle cell differentiation, and in the fibre type context, conversion to slow (oxidative) muscle phenotype (Musarò et al, 1999;Semsarian et al, 1999;Bigard et al, 2000;Delling et al, 2000). It has been reported that activated calcineurin mediates the hypertrophic effect of IGF-1 (Musarò et al, 1999;Semsarian et al, 1999). However, there is compelling evidence, including transgenic and knock-out data, to show that calcineurin has no effect on muscle hypertrophy but that the hypertrophic effect of IGF-1 is mediated by the PI3K pathway as detailed earlier (Naya et al, 2000;Bodine et al, 2001b;Rommel et al, 2001;Pallafacchina et al, 2002).…”
Section: Fibre Types: Coordinated Isoform-specific Expressionmentioning
confidence: 99%
See 2 more Smart Citations